2023
DOI: 10.1108/he-08-2022-0067
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review on mHealth related research during the COVID-19 outbreak

Abstract: PurposeUsing smart mobile devices, called mobile health (mHealth), facilitates providing health services, speeds up the process and reduces the costs and complications of direct services. Also, mHealth has many capabilities and applications in epidemic and pandemic outbreaks. This study aimed to systematically review the mHealth adoption researches in epidemic/pandemic outbreaks and provide some suggestions for future research for tackling for COVID-19.Design/methodology/approachThe results produced in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The ever-increasing prevalence of mental health disorders is subsequently resulting in an ever-increasing burden on mental health services globally (WHO, 2022b; Bower et al , 2023). Due to need outweighing capacity, and spurred on in light of the COVID-19 pandemic, a plethora of digital interventional resources have been designed, and implemented, to alleviate the burden upon mental health services and increase access to support for those in need (Adans-Dester et al , 2020; Cao et al , 2022; Alam et al , 2023; Lu et al , 2023). A variety of interventions have proven efficacious, such as mHealth apps (Kruse et al , 2022; Denecke et al , 2022; Dufoe, 2023), online support groups (Bauman and Rivers, 2023; Sharma et al , 2023), symptom checkers (Wallace et al , 2022; Pairon et al , 2023) and online talking therapies (Khan et al , 2022) to name but a few.…”
Section: Introductionmentioning
confidence: 99%
“…The ever-increasing prevalence of mental health disorders is subsequently resulting in an ever-increasing burden on mental health services globally (WHO, 2022b; Bower et al , 2023). Due to need outweighing capacity, and spurred on in light of the COVID-19 pandemic, a plethora of digital interventional resources have been designed, and implemented, to alleviate the burden upon mental health services and increase access to support for those in need (Adans-Dester et al , 2020; Cao et al , 2022; Alam et al , 2023; Lu et al , 2023). A variety of interventions have proven efficacious, such as mHealth apps (Kruse et al , 2022; Denecke et al , 2022; Dufoe, 2023), online support groups (Bauman and Rivers, 2023; Sharma et al , 2023), symptom checkers (Wallace et al , 2022; Pairon et al , 2023) and online talking therapies (Khan et al , 2022) to name but a few.…”
Section: Introductionmentioning
confidence: 99%
“…More hospitals are looking at the advantages of mobile health (mHealth) due to rising healthcare expenses and the desire for better care at home. They are seeking better communication between doctors and patients, especially those in more remote locations, as well as better utilisation of medical facilities like wireless data transmission, short message service and ease of connection with regular healthcare providers (Alam et al, 2023). Better communication enhances services that prevent patients from contracting serious forms of disease.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review has shown that mHealth has been successfully deployed to promote health services during the COVID-19 pandemic ( 4 ). Another systematic review identified mHealth as a very suitable alternative to patient-physician contacts during the COVID-19 pandemic ( 31 ).…”
Section: Introductionmentioning
confidence: 99%